Memória iconográfica: uma análise da representação das imagens fotográficas de negros/as nas universidades públicas do estado da Paraíba. - Mota, Ana Roberta Sousa (2012)
Analyzes images as part of the iconographic memory of graduates of undergraduate healthcare three institutions, focusing on the plates exposed graduation in the hallways and hospitals of the Federal University of Paraíba (UFPB), Federal University of Campina Grande (UFCG) and the State University of Paraiba (UEPB) was configured with general objective of this study. The phenomenon studied elicited a mixed approach articulating the qualitative and quantitative approach. The universe of the study covered three public universities in the state of Paraíba: UFPB (Health Sciences Center, University Hospital Lauro Wanderley and Health Sciences Center - Campus - Joao Pessoa / PB); UFCG (Biological and Health Sciences - Campus - Campina Grande / PB) and; UEPB (Hospital Universitário Alcides Carneiro, Center for Biological and Health Sciences - Campina Grande / PB). The corpus of analysis consisted of 13 images photographic selected from a total of 1190 images extracted from 174 plates of graduation in the iconographic memory of the 13 courses identified from the historical view of the images covering the period 2000 to 2010. Images were collected using a scanner and a camera. For identification of black people in memory of iconographic images of the courses, were used as criteria for analyzing black phenotypes. The analysis of images was performed based on the model of Smit (1996) for documentary analysis of images and the theoretical framework. To analyze the images, it took three different types of data, collected from the plates exposed for graduation in the halls of hospitals and universities, requested from the competent and pro-rectors responsible for the registration of (the) students in the courses and investigated; available on the sites of fulfilling the selection processes of the universities, in order to know the competition of the courses considered high prestige. The material for analysis is the result of a "heteroclassification" assigned by the researcher with the observation and identification of phenotypes Negroid and a self-classification (self-identification), given by the respondent, when asked spontaneously. The results indicate that the majority of (the) student (s) of the courses analyzed are predominantly white, and that racial inequality in the prestigious courses in Brazilian public universities, affect (the) black (s), especially in the Paraíba, requiring a radical change in the mechanisms of inclusion. (In) visibility of black (s) in public universities can be interpreted as a fact that little note, is seldom discussed, or if you want to discuss. It is considered that the poor presence of blacks these universities can not be solved only with an isolated action, but with public policies that benefit not only part of the population, but all of it, regardless of color, race or social status.